Teacher's Understanding of Minimum Competence Assessment and Its Impact on Assessment Conducted in Class - Ernawati, Ernawati; A. Ghani, Abdul Rahman; Trisnawati, Ratna Dwi; Malik, Zein Abdulloh (Universitas Negeri Semarang, 2023)
Misconceptions in assessment can lead to low quality of education. Previous research revealed that the misconceptions experienced by teachers, schools and parents in implementing the National Assessment policy had different impacts. This study aims to describe teachers' understanding of the Minimum Competency Assessment and its impact on assessments conducted in class. The data collection technique used a semi-structured interview method with seven MTs Muhammadiyah PPTQ Ahmad Dahlan teachers. The results of the study reveal that the teacher's understanding of the Minimum Competency Assessment is divided into translation, interpretation and extrapolation understanding. In addition, the assessment carried out in class by informants with an understanding of translation has not changed after the implementation of the Minimum Competency Assessment policy. Informants with an understanding of interpretation changed their assessments, while informants with an understanding of extrapolation felt there was no need to change the assessments carried out in class because they wanted to provide an overview of the actual abilities of students.